Modeling of the three phase distribution industrial network using Matlab/Simulink / Mashirwan Shafi'i - Shafi'i, Mashirwan (2002)
Harmonic distortion is not a new phenomenon. Concern over harmonic distortion emerged during the early history of ac power systems. Widespread applications of power electronic-based loads continue to increase concerns oner harmonic distortion. Harmonic problems have sparked research that has led to much of the present-day understanding of power quality problems.